Ecology of blood stream infection and antibiotic resistance in intensive care unit at a tertiary care hospital in North India - Chand Wattal (Brazilian Journal of Infectious Diseases, 2014)
Objective: To analyse the prevalent microorganisms and their antimicrobial resistance among intensive care unit patients in a tertiary care centre in New Delhi. Methods: A retrospective study of all consecutive blood cultures from various intensive care unit patients in the hospital during four years (January 2008 to December 2011). Antibiotic consumption data in the intensive care units were also analysed during the same period. Results: Out of the total 22,491 blood cultures processed, 2846 samples were positive and 3771 microorganisms were isolated. The blood culture positivity was estimated as 12.7% of which 67.5% were monomicrobial and 32.5% polymicrobial infections. Gram negative bacilli, Gram positive cocci, and fungi were isolated in 49%, 33%, and 18% cases, respectively. Coagulase negative staphylococcus was the commonest single isolate followed by Candida spp. A drastic shift in the distribution of Candida spp. towards nonalbicans along with high resistance to azole group of antifungals suggest echinocandins for the empiric therapy of candidemia. High penicillin resistance in Gram positive isolates suggest vancomycin, linezolid and tigecycline as the options for empiric therapy, whereas tigecycline and colistin are the only options remaining for highly resistant Gram negative isolates. Aminoglycosides were observed to have better sensitivity and reduced usage when compared with cephalosporins and β-lactam + β-lactam inhibitor combinations. Conclusions: High frequencies of multidrug resistant organisms were observed in intensive care units which is a warning as to use the only few effective antimicrobials wisely to reduce selective pressure on sensitive strains. Keywords: Infection in ICU, Multi-drug resistance, Antibiotic consumption, Drug resistant Candida species